The Effect of Peritoneal Repair or Non-Repair on Complications after open Appendectomy - R Hosseinpour; S Mehrabi; SK Nikooei; SH Salaminia; MB Jahantab; CH Zakaria Nezhad Kasgari (Armaghane Danesh Bimonthly Journal, 2023)
Background & aim: Appendicitis is the most common condition of emergency surgery. Complications after appendectomy include skin complications, infection, postoperative pain, hernia and obstruction. There is a difference of opinion among surgeons on peritoneal repair after abdominal surgery. Therefore, we aimed here to evaluate the effect of peritoneal repair versus non-repair in appendectomy patients in terms of postoperative complications.